The effectiveness of motivational factors for government sector: a research in Jabatan Audit Negara Cawangan Negeri Selangor / Halimatul Sa’adiah Ahmad - Ahmad, Halimatul Sa’adiah (Faculty of Business and Management, 2009)
This research is conducted to identifying the effectiveness of motivational factors toward the employees that works in the government sectors. This research can help the employees to identify which factors is more influence to them. Several motivational factors that can influence the workers such good working environment, good wages, appreciation for work done and interesting work have been identified in order to investigate whether or not these factors have significant relationship with motivational factors.